Gastrodiplomasi Korea Selatan di Indonesia melalui Ekspor Produk Makanan Korea Selatan Periode 2020-2022 - Mutiara Fidela Hanifah; Hesti Rosdiana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Gastrodiplomacy is the diplomacy used by South Korea throughout the world, including Indonesia. Diplomatic activities can basically increase the country's export activities. During the Covid-19 pandemic, South Korean export activities in Indonesia experienced a decline. Therefore, this research aims to increase exports of South Korean food products in Indonesia during the Covid-19 pandemic through South Korean Gastrodiplomacy in Indonesia. In answering these problems, the concepts of gastrodiplomacy and new public diplomacy are used. The research method used is qualitative which aims to find out in depth by exploring and understanding the central issues in the research. The aim of this research is to determine the increase in exports of South Korean food products in Indonesia during the Covid-19 pandemic through gastrodiplomacy. The results of this research are an increase in export activities of South Korean food products in Indonesia and also an increase in the number of Indonesian people's interest in Korean food which directly encourages an increase in export activities of South Korean food products to Indonesia which continues to increase every year.